Integrative Modeling Reveals Annexin A2-mediated Epigenetic Control of Mesenchymal Glioblastoma - Kling, Teresia; Ferrarese, Roberto; Ó hAilín, Darren; Johansson, Patrik; Heiland, Dieter Henrik; Dai, Fangping; Vasilikos, Ioannis; Weyerbrock, Astrid; Jörnsten, Rebecka; Carro, Maria Stella; Nelander, Sven (EBioMedicine, 2016)
Glioblastomas are characterized by transcriptionally distinct subtypes, but despite possible clinical relevance, their regulation remains poorly understood. The commonly used molecular classification systems for GBM all identify a subtype with high expression of mesenchymal marker transcripts, strongly associated with invasive growth. We used a comprehensive data-driven network modeling technique (augmented sparse inverse covariance selection, aSICS) to define separate genomic, epigenetic, and transcriptional regulators of glioblastoma subtypes. Our model identified Annexin A2 (ANXA2) as a novel methylation-controlled positive regulator of the mesenchymal subtype. Subsequent evaluation in two independent cohorts established ANXA2 expression as a prognostic factor that is dependent on ANXA2 promoter methylation. ANXA2 knockdown in primary glioblastoma stem cell-like cultures suppressed known mesenchymal master regulators, and abrogated cell proliferation and invasion. Our results place ANXA2 at the apex of a regulatory cascade that determines glioblastoma mesenchymal transformation and validate aSICS as a general methodology to uncover regulators of cancer subtypes.
CRIS-Team Scopus Importer:2024-03-07
Keywords: Annexin A2; Brain tumor stem cells; Data integration; Epigenetic regulation; Glioblastoma; Master regulators of cancer cell phenotypes; Mesenchymal transformation; New methods for integrative data analysis; Partial correlation based networks; Spare inverse covariance selection